-(4 + 10x) - 10x + 17 = 49- 4 - 10x - 10x + 17 = 49- (10x+10x) + (17 - 4) = 49-20x + 13 = 49-20x = 49 - 13-20x=36x = 36 : (-20) = - ¹⁸/₁₀х = - 1,8======================-( 4 + 10 * (-1,8)) - 10* (-1,8) +17 = 49- (4 - 18) + 18 + 17 = 49- ( - 14) + 35 = 49 14 + 35 = 4949 = 49(44 - 10х)+5х - 43 = 4944 - 10х + 5х - 43 = 49-5х + 1 = 49-5х = 49 - 1-5х = 48х = 48 : (-5) = - ⁴⁸/₅х= -9,6========================(44 - 10 * (-9,6) ) + 5* (-9,6) - 43 = 49(44 + 96) - 48 - 43 = 49140 - 91 = 4949=49149 - 18х +3х + 5х =43149 - (18х - 3х - 5х) = 43149 - 10х = 43-10х = 43 - 149-10х = - 106 | *(-1)10x=106x= 106 : 10х= 10,6=====================149 - 18 *10,6 +3*10,6 +5*10,6 = 43149 + (-18 + 3 + 5)*10,6 = 43149 + (-10) *10,6 = 43149 - 106 = 4343=43